2020
DOI: 10.1002/ente.202000591
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Composite Insulation System of Hollow Glass Microspheres and Multilayer Insulation with Self‐Evaporating Vapor Cooled Shield for Liquid Hydrogen Storage

Abstract: The efficient storage method of hydrogen energy is a major concern in its practical application. Compared with other hydrogen storage methods, liquid hydrogen (LH2) storage has the advantages of high energy storage density and low storage pressure. However, the temperature of LH2 is significantly lower than room temperature, and heat leakage causes it to evaporate continuously. Thus, an efficient thermal insulation technology is a key to LH2 storage. Herein, based on the traditional multilayer insulation (MLI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[ 8 ] In recent years, researchers have begun to focus on the application of HGM in the field of low‐temperature insulation. [ 9–11 ] Jin et al [ 12 ] compared the thermal conductivity of insulation materials, and the results showed that the thermal conductivity of HGM was better than most of the powders, and the thermal conductivity of HGM was better than that of 10 layers of MLI at pressures higher than 1.33 Pa. Analytical calculations by Wang [ 13 ] showed that the solid thermal conductivity of HGM increases with the increase of true density, and the gas thermal conductivity increases with the increase of pressure, occupying the main part of heat transfer in the range of 1–100 Pa. NASA [ 14,15 ] found through evaporation test experiments that the thermal insulation performance of HGM is better than that of perlite at all vacuum levels, and the thermal insulation performance of HGM is better than that of 60‐layer MLI at pressures greater than 4 Pa. [ 16 ] The above studies have shown that HGM has better insulation performance and vacuum adaptability than other insulation materials. However, for different types of HGMs with different compositions, particle sizes, densities, and other physical properties, obtaining the quantitative insulation effect of an HGM requires a long time of liquid evaporation tests.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] In recent years, researchers have begun to focus on the application of HGM in the field of low‐temperature insulation. [ 9–11 ] Jin et al [ 12 ] compared the thermal conductivity of insulation materials, and the results showed that the thermal conductivity of HGM was better than most of the powders, and the thermal conductivity of HGM was better than that of 10 layers of MLI at pressures higher than 1.33 Pa. Analytical calculations by Wang [ 13 ] showed that the solid thermal conductivity of HGM increases with the increase of true density, and the gas thermal conductivity increases with the increase of pressure, occupying the main part of heat transfer in the range of 1–100 Pa. NASA [ 14,15 ] found through evaporation test experiments that the thermal insulation performance of HGM is better than that of perlite at all vacuum levels, and the thermal insulation performance of HGM is better than that of 60‐layer MLI at pressures greater than 4 Pa. [ 16 ] The above studies have shown that HGM has better insulation performance and vacuum adaptability than other insulation materials. However, for different types of HGMs with different compositions, particle sizes, densities, and other physical properties, obtaining the quantitative insulation effect of an HGM requires a long time of liquid evaporation tests.…”
Section: Introductionmentioning
confidence: 99%